Common Fixed Point Theorems Using Rational Contraction In Soft Compact Metric Spaces - et. al., Ramakant Bhardwaj, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The most important aim of the prevailing paper is searching for a new fixed point theorems using rational Contractions in the setting of soft compact metric spaces which generalizes the results of Sayyed In particular we investigate the soft compact space based rational expression with soft sets and get some new results